2020
DOI: 10.3390/ma13102392
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Moisture on the Mechanical, Morphological and Thermogravimetric Properties of Mineral Wool Made from Basalt Glass Fibers

Abstract: Mineral wool made from basalt fibers is frequently used as an insulating material in construction systems. In this study, both unused mineral wool and wool obtained from the softened roofing area were comprehensively analyzed in a laboratory using different characterization techniques. Firstly, the initial water content and compressive strength at 10% deformation were determined. Secondly, microstructure and surface chemical composition were analyzed by scanning electron microscopy (SEM) equipped with energy d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Several small peaks were identified that confirm the presence of calcium (2.91%), magnesium (2.71%), sodium (2.29%), iron (2.07%), potassium (0.24%), titanium (0.24%), barium (0.07%), and cobalt (0.05%). Similar SEM-EDAX spectra for DMFM fiber and BF were reported by other researchers [52] , [53] .
Fig.
…”
Section: Resultssupporting
confidence: 88%
“…Several small peaks were identified that confirm the presence of calcium (2.91%), magnesium (2.71%), sodium (2.29%), iron (2.07%), potassium (0.24%), titanium (0.24%), barium (0.07%), and cobalt (0.05%). Similar SEM-EDAX spectra for DMFM fiber and BF were reported by other researchers [52] , [53] .
Fig.
…”
Section: Resultssupporting
confidence: 88%
“…These spectra are consistent with the ones from literature as microplastic 90 , 106 . Among these, an important class is that of fibreglass which includes different kind of plastic all of them characterized by Carbon (C), Oxygen (O), and Silicon (Si) 107 , 108 ( https://www.nrc.gov/docs/ML0530/ML053040493.pdf ) where the glass fibres are commonly added to reinforce plastic structures 109 , 110 . This specific kind of plastic is part of the components detected in the present study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as shown in our previous study, natural ageing under high humidity and thermal fluctuations can strongly influence the surface morphology and chemical composition of fibrous insulation material covered with plasticized PVC. 14 A probable reason for the deterioration of the insulation was the damaged waterproofing PVC membrane. To ensure a fully functional and repair-free lifetime of a building, the degradation and durability estimation of covering water-repellent PVC-P membranes must be considered.…”
Section: Introductionmentioning
confidence: 99%